The Research Assessment Exercise - Broadhead, Lee-Anne; Howard, Sean (Education Policy Analysis Archives, 1998)
In this article it is argued that the recent Research Assessment Exercise (RAE)--undertaken by the United Kingdom's Higher Education Funding Councils (HEFC)--is part of a much larger process of assessment in education generally. By taking the RAE as its focus, this article uses a Foucaultian analysis to amplify the nature and practice of disciplinary power in the setting of Higher Education. Foucault's notion of an "integrated system" of control and production, with its routine operation of surveillance and assessment--and its dependence on coercion and consent--is directly applied to the RAE. The impact on research and teaching is discussed. The critical response of academics to the exercise has failed to challenge the process in any fundamental way. it is argued here that this failure is a reflection of the degree to which disciplinary logic is embedded in the academic system.